Determination of electrical conductivity and pH from the different type honey suction pump - Siti Nur Atikah, Mohd Noor (2019)
In this thesis presents the electrical conductivity and pH values of stingless bee honey samples collected from two different suction circulation; diaphragm vacuum pump and peristaltic pump was investigated. The honey samples were collected from the area of Bukit Goh, Kuantan, Pahang. Physicochemical analyses of parameters such as electrical conductivity and pH values have an important part in defining the overall properties of the honey and acquiring the quality of stingless bee honey in both type of pump. The data from the electrical conductivity shows that the honey samples from the diaphragm vacuum pump and peristaltic pump are 0.48 – 0.95 mS/cm and 0.25- 0.80 mS/cm respectively. Meanwhile, the data from the pH shows that the honey samples from the diaphragm vacuum pump and peristaltic pump are in range of 3.32 – 3.53 and 3.39 – 3.5 respectively. From the research, the value of electrical conductivity of honey sample from diaphragm vacuum pump is slightly higher than peristaltic pump but the pH values of the both pump are same in values. In conclusion, the peristaltic pump can maintain the physicochemical characteristics of stingless bee honey eventhough the both pumps have different in many ways.